Neuroendocrine tumour of a larynx in 70-year-old man: a rare entity and a diagnostic challenge - Shabbir, Nida; Singh, Ajay K.; Chandra, Manish; Qayoom, Sumaira (International Journal of Research in Medical Sciences, 2024)
Neuroendocrine tumours of the larynx are rare yet neuroendocrine tumors is the second most common larynx tumour. According to the World Health Organization (WHO) 2022 classification, neuroendocrine tumours (NET) can be classified into well-differentiated, moderately differentiated and poorly differentiated. Well-differentiated NETs (typical carcinoids) of the larynx are rare and largely published as case reports. We present a case of a 70-year-old male with a history of hoarseness of voice for 1 year. Grossly, the tumour was globular and encapsulated. Based on histopathological features and immunohistochemistry results, the final diagnosis of a well-differentiated Neuroendocrine tumour was rendered. For carcinoid tumours of the larynx, conservative surgical resection is the preferred treatment without elective neck dissection. This tumour has a favourable prognosis, rare recurrences, and minimal metastasis.